Athletic identity, anxiety, and depression in moderate to highly specialized female adolescent volleyball players - Clark, V. C.; Ulman, S. M.; Erdman, A. L.; Gale, E. B.; Janosky, J.; Stapleton, E. J. (Frontiers in Psychology, 2025)
Introduction: Individuals strongly tied to their athletic sense of self, athletic identity, may have increased sport specialization and behaviors elevating injury risk, overtraining, and mental health concerns. No known studies have explored the relationship between athletic identity, specialization, and youth athletes` mental health concerns, specifically anxiety and depression. This study assessed the relationship between athletic identity, specialization, and mental health symptoms among female, high school athletes.